Non-HDL-C/HDL-C ratio is associated with carotid plaque stability in general population: A cross-sectional study - Wang, Anran; Li, Yapeng; Zhou, Lue; Liu, Kai; Li, Shaohua; Zong, Ce; Song, Bo; Gao, Yuan; Li, Yusheng; Tian, Chuansheng; Xing, Yurong; Xu, Yuming; et al. (Frontiers in Neurology, 2022)
Background Carotid atherosclerosis, especially the rupture of unstable plaques, plays an important role in the development of stroke. A novel lipid ratio, the non-high-density lipoprotein cholesterol (non-HDL-C)/high-density lipoprotein cholesterol (HDL-C) ratio, contains both atherogenic and anti-atherogenic particle information, and has been shown to be associated with carotid atherosclerosis. However, there is no data on evaluating the association between non-HDL-C/HDL-C ratio and carotid plaque stability. Methods This study was carried out on 27,436 urban workers aged 20 years or older who participated in a comprehensive health screening between January 2016 and December 2017. Carotid plaque stability was assessed using ultrasonography. Multinomial logistic regression models were used to explore the relationship between the non-HDL-C/HDL-C ratio and carotid plaque stability by odds ratios (ORs) and 95% confidence intervals (CIs). Subgroup and sensitivity analyses were performed to verify the robustness of the results. Results Carotid plaque was detected in 7,161 (26.1%) participants, with stable and unstable plaque accounting for 3,277 (11.9%) and 3,884 (14.2%), respectively. The prevalence of stable carotid plaque substantially increased with increasing non-HDL-C/HDL-C ratio quartile levels (p for trend < 0.001) and with a similar association for unstable carotid plaque (p for trend < 0.001). The mean non-HDL-C/HDL-C ratios (mean ± SD) of non-carotid plaque (2.9 ± 1.1), stable carotid plaque (3.2 ± 1.2), and unstable carotid plaque (3.4 ± 1.4) gradually increased (p < 0.001). In multinomial logistic regression, ORs (95% CIs) for the highest vs. lowest quartile of the non-HDL-C/HDL-C ratio were 1.70 (1.48–1.95) between stable carotid plaques and no carotid plaque, 2.34 (2.06–2.67) between unstable carotid plaques and no carotid plaque, and 1.38 (1.18–1.61) between unstable carotid plaques and stable carotid plaque, after adjusting for common cardiovascular risk factors. The results of subgroup analysis and sensitivity analysis were similar. Conclusion Our findings suggested that the non-HDL-C/HDL-C ratio was significantly associated with carotid plaque stability and might be a useful indicator for the early identification of high-risk carotid plaque.